Comparison of feed consumption of pigs in two lines - Wheat, J.D.; Kropf, Donald H.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs in the control line ate more, grew faster, and were less efficient than those in the select line.
Swine Day '76 is known as Swine Day, 1976
Keywords: Swine; Control vs. select line